Layered management approach to cyber security of IoT solutions - Ozdogan, Erdal; Das, Resul (Inderscience Enterprises Ltd, 2023)
The Internet of Things consists of devices, each with its own vulnerabilities and interconnected by various technologies. This broad spectrum, a combination of old and new technologies, shows that there are many aspects to consider in ensuring IoT security. Besides the vulnerabilities inherited from pre-IoT technologies, there are a wide variety of IoT-specific vulnerabilities. The existence of large attack surfaces for cyber threat actors exposes IoT to a variety of attacks, from simple to complex. Developing defence strategies against this wide range of attacks is possible with a systematic approach. In this study, threats to IoT are examined from the perspective of IoT layered architecture, and an IoT Security Management Model is proposed as a comprehensive solution strategy. Also, based on the developed model, countermeasures related to IoT security have been proposed.
Keywords: IoT security; IoT security architecture; IoT attacks; IoT attack surfaces; layered management approach